IMPACT OF FASHION INFLUENCER DETERMINANTS ON BUILDING FUNCTIONAL AND SYMBOLIC IMAGE OF BRAND - Lohchab, Kirti; Chauhan, Anand; Kumar, Raj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study article specifically aims to look at how fashionistas affect the symbolic and functional brand image. This work approaches the quantitative analysis of the data acquired via surveys. The primary focus of the study is on consumer perceptions of companies relying on interactive social media components and the trustworthiness of fashion influencers. While visual appeal and engagement-driven material help to enhance brand image, fashion influencer credibility and social media following significantly influence customer view of a company’s fashion-ability. This paper increases knowledge of fashion industry digital marketing dynamics and emphasizes the part influencers play in building brand image in the digital environment.